Índices antropométricos como predictores de obesidad y riesgo metabólico en estudiantes de la Unidad Educativa del Milenio Bernardo Valdivieso–Loja - Robles Cuenca, Diana Alexandra (2022)
Obesity and overweight are the main causes of morbidity and mortality in Ecuador and the world. This research aims to determine anthropometric indices as predictors of obesity and metabolic risk in students at the Bernardo Valdivieso- high school in Loja; through the body mass index (BMI), waist-hip ratio (WHR), and waist-height ratio (*WHR). Descriptive type study, cross-sectional cohort, prospective, quantitative approach, population 281 adolescents aged 14 to 18 years; by taking anthropometric measurements of height (cm) and weight (kg) to obtain BMI; *WHR by dividing waist circumference by height; and waist and hip circumference were calculated to obtain the WHR, determining the risk of metabolic syndrome (MS). The results obtained according to the BMI showed: 80.43% (n=226) have normal nutritional status more likely in women; followed by overweight 11.39% (n=11) higher in men; low weight 4.63% (n=13) predominant in women; grade I obesity 2.49% (n=7) higher in men; grade II obesity 0.71% (n=2) for both sexes and grade III 0.36% (n=1) higher in women; these nutritional alterations predominated in 16-year-olds, women (n=68) and men (n=49). When determining the metabolic risk using *WHR, 74.01% (n=208) did not present risk, and 25.99% (n=73) are at risk, being frequent in women 13.17% (n=37). Regarding WC (waist circumference), 88.97% (n=250) have no risk, 7.12% (n=20) are at very high risk, and 3.91% (n=11) high risk, being more common in women with 5.34% (n=15) and 3.56% (n=10) respectively. According to the WHR, 61.57% (n=173) do not present risk and 38.43% (n=108) present risk, mainly in men 22.06% (n=62). In addition, the correlation is checked using the non-parametric Spearman's Rho test between obesity and metabolic risk